Mr pink-whistle's party - Blyton, Enid (Bounty Books London, 2014)
"Enid Blyton's most popular characters get up to all sorts of mischief in short stories for younger readers. Ideal for children's first ventures into reading alone, Happy Days is a magical and captivating collection filled with lovable characters." --Publisher description